My History or Our History? Historical Revisionism and Entitlement to Lead - Haas, Nicholas; Lindstam, Emmy (Cambridge University Press, 2023)
Ongoing,spirited debates from around the globe over statues,street names,symbols,and textbooks call for a greater understanding of the political effects of different historical representations. In this paper,we theorize that inclusive (exclusive) historical representations can increase (decrease) marginalized group members' perceived centrality to the nation,entitlement to speak on its behalf,and likelihood of becoming leaders. In an online experiment in India (),we randomly assign participants exercises sourced from official state textbooks containing either an exclusive,inclusive,or a neutral representation of history. We subsequently assess the supply of and demand for Muslim leadership using both an original,incentivized game and additional survey and behavioral measures. We find that inclusive historical narratives increase Muslim participants' perceived centrality and entitlement,desire to lead,and demand for real-world Muslim leaders. Battles over history can carry consequences for the leadership ambitions of marginalized individuals,for themselves and their communities. © The Author(s),2023. Published by Cambridge University Press on behalf of the American Political Science Association.
Keywords: ODS 10 - Reducción de las desigualdades